EFFECTIVENESS OF A GAMIFICATION APPLICATION IN LEARNING MANDARIN AS A SECOND LANGUAGE - Mun Pei Ng; Norlidah Alias; Dorothy DeWitt (UUM Press, 2022)
Purpose - Gamification is an effective method to boost students' academic achievement and engagement in second language learning. This study aimed to test the effectiveness of the gamification application, Class Dojo, among Year 4 pupils who are learning Mandarin as a Second Language (MSL). It also sought to investigate how the MSL learners became more engaged in learning Mandarin when using Class Dojo. Methodology - A quasi-experimental design with a pre-test and a post-test was conducted to collect data among thirty (30) Year 4 pupils enrolled in the MSL course. The pre-test and a post-test were used to determine the effectiveness of Class Dojo in elevating the pupils' achievement in learning MSL. The mean scores of the pre-test and post-test were compared and analyzed using t-tests to determine if they were significantly different. Data from observations, the pupils'self-reflective journal, and the collection of 'Dojo Points' were grouped into five main themes and analyzed in order to investigate how the participants were engaged in learning MSL. Findings - The findings showed that there was a significant improvement in the academic results of the participants. The pupils' high rate of attendance, task completion, frequent Mandarin usage, positive behavior, and favorable perceptions of Class Dojo indicated that they were engaged in learning in the MSL class. Significance - The findings of this study provide MSL educators and instructional designers with information to consider whether gamification applications could be used as an effective teaching tool or virtual class management tool to enhance pupils' engagement and improve learning outcomes.